Bendamustine in combination with pomalidomide and dexamethasone in relapsed/refractory multiple myeloma: A phase II trial. (2nd May 2022) - Kumar, Sudhir; Sharma, Atul; Malik, Prabhat Singh; Gogia, Ajay; Pathak, Neha; Sahoo, Ranjit Kumar; Gupta, Ritu; Prasad, Chandra Prakash; Kumar, Lalit
Summary: Treatment of patients with resistant/refractory multiple myeloma (MM) is an unmet need. In this phase II study, we evaluated the role of bendamustine, pomalidomide and dexamethasone combination in this setting. Between February 2020 and December 2021, 28 patients were recruited. Patients received bendamustine 120 mg/m 2 day 1, pomalidomide 3 mg days 1–21, and dexamethasone 40 mg days 1, 8, 11, 22, regimen given for a maximum of six cycles. The median (range) age of the patients was 54 (30–76) years and 15 (53.6%) were males. Patients had received a median (range) of three (two–six) prior lines and 85.7% were refractory to both lenalidomide and bortezomib. The primary end‐point was the overall response rate (ORR) defined as ≥partial response after at least three cycles. Secondary objectives were toxicity, progression‐free survival (PFS), time to progression and overall survival (OS). An intent‐to‐treat analysis was done. An ORR of 57.6% was achieved. Patients with extramedullary myeloma had a better response rate. At a median follow‐up of 8.6 months, the median PFS and OS were 6.2 and 9.7 months respectively. Toxicity was manageable; mainly haematological (neutropenia, 46.4%; anaemia, 42.8%; and thrombocytopenia, 7.1%). Bendamustine, pomalidomide and dexamethasone could be a novel combination for the heavily pretreated, lenalidomide‐refractory myeloma population.